Public accountancy profession : assurance principles, professional ethics, good governance - Cabrera, Ma. Elenita Balatbat (Manila, Philippines : GIC Enterprises & Co. Inc., 2013)
A rich assortment of skill building assignments are provided to help the readers strengthen their analytical and communication skills necessary for successful careers as professional accountants.
Unit 1. Overview of a CPA's professional practice -- 2. Legal, regulatory and Ethical requirements -- 3. Regulation within the Accounting Firm -- 4. Risk-Based Audit of financial statements: Phase I- Risk Assessment -- 5. Risk based Audit of Financial statements: Phase II - Risk Response -- 6. Risk based Audit of Financial statements: Phase III reporting -- 7. Auditing in a computer Information systems environment -- 8. Other services and reports
Includes bibliographical references.
Keywords: ACCOUNTING -- STUDY AND TEACHING